Spikelet differentiation and degeneration in rice varieties with different panicle sizes. (9th August 2021) - Liu, Kun; Chen, Yun; Huang, Jian; Qiu, Yuanyuan; Li, Siyu; Zhuo, Xinxin; Yu, Feng; Gao, Jie; Li, Guoming; Zhang, Weiyang; Zhang, Hao; Gu, Junfei; et al.
Abstract: An essential feature of modern high‐yielding rice varieties is the production of numerous spikelets, but the physiological mechanism underlying spikelet formation in these varieties remains unclear. In this study, we explored the characteristics of spikelet differentiation and degeneration and the relevant physiological characteristics of rice varieties with different panicle sizes. The regulatory effects of alternate wetting and moderate soil drying (AWMD) on spikelet formation were also measured. We determined that the high spikelet number per panicle and grain yields of large‐panicle rice varieties were primarily due to a higher number of differentiated and surviving secondary spikelets. Furthermore, shoot dry weight, plant nitrogen (N) uptake, plant N concentration, non‐structural carbohydrate (NSC) accumulation in stems, leaf area, and leaf photosynthetic rate from branch differentiation stage (BDS) to spikelet differentiation stage (SDS) were positively correlated with the number of differentiated secondary spikelets per panicle. Plant N concentration, NSC accumulation in stems, and leaf photosynthetic rate at pollen mother cell meiosis (PMC) were negatively correlated with the number of degenerated secondary spikelets. Finally, the number of differentiated secondary spikelets of Huaidao 5 (small panicle size) and Yongyou 2640 (large panicle size) varieties was promoted by 19.2% and 6.6%, and the number of degenerated secondary spikelets was reduced by 14.4% and 6.3%, respectively, under AWMD treatment compared to continuously flooded treatment. Prominent spikelet formation under AWMD resulted from the shoot dry weight, plant N uptake, plant N concentration, NSC accumulation in stems, leaf area, and leaf photosynthetic rate. Collectively, improvements in these key aboveground indices mentioned above during the BDS to SDS and the plant N concentration, NSC accumulation in stems, and leaf photosynthetic rate at the PMC stage would benefit spikelet formation by promoting differentiation and reducing degeneration of secondary spikelets, thereby enhancing yield of large‐panicle rice varieties. Abstract : High numbers of differentiated secondary spikelets contribute to high grain yields. Improving plant N concentration, NSC accumulation in stems and leaf photosynthetic rate during BDS–SDS and PMC can promote secondary spikelet differentiation and reduce degeneration, respectively. AWMD can promote the differentiation of secondary branches and spikelets and reduce spikelet degeneration, ultimately leading to larger spikelets and higher yields.